Preventive maintenance characteristics towards optimal maintenance performance: A case study of office buildings - Au-Yong, Cheong Peng; Ali, Azlan Shah; Ahmad, Faizah (2014)
Lack of preventive measure is currently the problem that implicates poor building maintenance performance and issue on sustainability of buildings in Malaysia. Whereby, preventive maintenance is an effective approach to enhance the reliability and quality of a system and its components. This study seeks to investigate the characteristics of preventive maintenance towards the overall performance in building maintenance. Case study approach is adopted to identify the maintenance characteristics and aspects that lead to good performance. The research findings demonstrate that the most significant maintenance characteristics towards overall performance are skill and knowledge of maintenance labour, quality of spare parts and materials, length of predetermined maintenance interval, skill and knowledge of maintenance manager, capability to adopt maintenance equipment and technique, budget allocation for acquisition of maintenance data, reliability of maintenance data, as well as frequency of monitoring and inspection. As a conclusion, the significant maintenance characteristics must be taken into consideration to achieve optimal maintenance performance. In order to improve the effectiveness of maintenance strategy and the maintenance performance, the study recommends practice and provision of communication platform such as meeting and customer satisfaction survey that involves all the key participants from clients to customers.